2017
DOI: 10.3748/wjg.v23.i9.1720
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumor of the stomach with axillary lymph node metastasis: A case report

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common type of gastrointestinal mesenchymal tumors, although metastasis to the perigastric lymph nodes is relatively rare, compared with liver or peritoneal metastasis. In this report, we describe a case of stomach GIST with a solitary simultaneous metastasis in the left axillary lymph node. A 68-year-old man was diagnosed with a large upper-stomach GIST, and computed tomography and positron emission tomography revealed masses in the left axilla and right me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…[ 56 ] Solitary lymph node metastasis mainly occurred in the perigastric node area, [ 57 , 58 ] but some appeared in extra-perigastric region or even distant area, which was named skip metastasis. [ 59 , 60 ] Sentinel node mapping are recommended in patients with EGC who underwent surgical excision to detect possible skip metastasis. [ 61 , 62 ] A single-skip metastasis located along the middle colic artery was unexpectedly detected in sentinel lymph node biopsy of EGC by Bara's group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] Solitary lymph node metastasis mainly occurred in the perigastric node area, [ 57 , 58 ] but some appeared in extra-perigastric region or even distant area, which was named skip metastasis. [ 59 , 60 ] Sentinel node mapping are recommended in patients with EGC who underwent surgical excision to detect possible skip metastasis. [ 61 , 62 ] A single-skip metastasis located along the middle colic artery was unexpectedly detected in sentinel lymph node biopsy of EGC by Bara's group.…”
Section: Discussionmentioning
confidence: 99%
“…We performed literature searches with Google scholar and PubMed from 2000 to 2018. The keywords used were “GIST,” “stomach,” and “lymph node metastasis.” Eight studies [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ] and 15 case reports were found ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…GISTs of the stomach with lymph node metastasis are very rare [ 1 ]. Previous studies reported surgical treatment with gastrectomy and systematic lymphadenectomy [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] ]. According to a recent review of current international clinical guidelines by JNCCS and ESMO [ 11 , 12 ], the recommended surgical strategy is as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introductiono A GIST (gastrointestinal stromal tumor) is a neoplasm that arises out of the GI tract 1 o GISTs are the most common mesenchymal tumors of the GI tract2 …”
mentioning
confidence: 99%